If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 3sqrt(X + 3 + -3) Multiply f * x fx = 3sqrt(X + 3 + -3) Reorder the terms: fx = 3qrst(3 + -3 + X) Combine like terms: 3 + -3 = 0 fx = 3qrst(0 + X) fx = 3qrst(X) Multiply qrst * X fx = 3qrstX Solving fx = 3qrstX Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 3qrstx-1X Simplifying f = 3qrstx-1X
| F(2065)=895+30g | | 3-6(-5y+4)=3(-y+1)-6 | | log^6x=3 | | 3(x-2)+7=3x+27 | | -19(2a-3b+8c)= | | 13x-2(4x-5)=66-3x | | 5z^2-37zy+42y^2=0 | | 72+24w=288 | | 3(4x-3)= | | 2ln(x)=4 | | 24+16p=4p | | 24x-32=24x+36 | | 5+2j=27 | | 50-82d-86-8d+7+4d= | | -5x+(2+x)= | | 5+2j=25 | | 6w^3y^6-3u^3w^2/6w^5 | | y=(2x+5)2 | | 27=5+2j | | q=p-30 | | -4.8(x+3)+6.5(x-1.2)=-25.09 | | 19+n=42 | | -4y+3x=28 | | 15+4n=63 | | 6x*7y= | | (a^-2b/ab^6)^-3 | | -5+9=a+5-7 | | X-53=27 | | 4b=80 | | 0.06=n(7) | | 11a=77 | | 8x+8=4x+2 |